Upaya Peningkatan Pelayanan Melalui Room Attendant di Hotel Grand Mercure Solo Baru - Octaviani Gita Putri; Bartolomeus Herawan Mintardjo; Dewi Hermawati Wahyuningsih; Denny Asmara; Aulia Firmansyah (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
One of the factors that influences guest satisfaction is service quality. One effort to improve service quality is through the Housekeeping Department, in the Room Attendant section. These efforts can be enhanced through management and operational levels. Therefore, it is important to know the efforts made by the Grand Mercure Solo Baru Hotel to improve the quality of hotel services through the Room Attendant section. The research approach used in this research is a qualitative research approach. Primary data through direct observation in the field, in-depth interviews with sources, Executive Housekeeper, Casual Housekeeping Supervisor, field documentation in the form of field photos, and official documents provided legally. Secondary data uses articles, books and so on. The research instruments used in this research were observation and in-depth interviews. Data were analyzed by data reduction, data presentation, drawing conclusions and verification, final conclusions. Based on research, it was found that efforts to improve the quality of room attendant services through the managerial level are to hold routine training every 4 months, tightening the SOP for Room Attendants. At the operational level, the focus is on employee attitudes towards guests, including a clean and neat appearance according to SOPs and behavior with the 5S principles (smile, greet, salute, be polite, courteous).